Selective Acceleration of O+ by Drift‐Bounce Resonance in the Earth's Magnetosphere: MMS Observations. Issue 2 (22nd February 2020) - Oimatsu, S.; Nosé, M.; Le, G.; Fuselier, S. A.; Ergun, R. E.; Lindqvist, P.‐A.; Sormakov, D.
Abstract: We studied O + drift‐bounce resonance using Magnetospheric Multiscale (MMS) data. A case study of an event on 17 February 2016 shows that O + flux oscillations at 10–30 keV occurred at MLT 5 hr and L 8–9 during a storm recovery phase. These flux oscillations were accompanied by a toroidal Pc5 wave and a high‐speed solar wind ( 550 km/s). The azimuthal wave number ( m ‐number) of this Pc5 wave was found to be approximately −2. The O + /H + flux ratio was enhanced at 10–30 keV corresponding to the O + flux oscillations without any clear variations of H + fluxes, indicating the selective acceleration of O + ions by the drift‐bounce resonance. A search for similar events in the time period from September 2015 to March 2017 yielded 12 events. These events were mainly observed in the dawn to the afternoon region at L 7–12 when the solar wind speed is high, and all of them were simultaneously identified on the ground, indicating low m ‐number. Correlation analysis revealed that the O + /H + energy density ratio has the highest correlation coefficient with peak power of the electric field in the azimuthal component ( E a ). This statistical result supports the selective acceleration of O + due to the N = 2 drift‐bounce resonance. Key Points: MMS observed the enhancement of O + /H + flux ratio in the magnetosphere during the recovery phase of a small storm Drift‐bounce resonance with low‐ m Pc5 waves is responsible for the selective acceleration of energetic O + The transverse Pc5 waves that selectively accelerated O + through the drift‐bounce resonance are driven by high‐speed solar wind